Temporary stimulator with voltage variable. Gastric pressure recording - Vitancurt, Gustavo; Vázquez, Enrique; Fernández, Ricardo; González, Daniel; Burstin, Jacobo (Cirugía del Uruguay, 1990)
The use is made of the temporary stimulator of the digestive tube to assess the rates of voltage and contractile force of the stomach. Permanently recorded was the proportional response and a threshold value.